IMPROVEMENT OF LGISTIC COMPANY PERFORMANCE THROUGH PLANNING, TEAM CAPABILITY AND SALES SUPORT - Caroline, Servita; Hariadi DP, Agustinus (Dinasti International Journal of Management Science, 2021)
The purposes of this research are to find out how strong and in what direction planning has an impact on team capabilities, sales support, team capabilities towards company performance, and sales support towards company performance. In this study, the data would be analyzed using the PLS-SEM method at two degrees of confidence which involved all employees at the company where the research was conducted, a total of 70 employee respondents. According to the findings obtained using two levels of confidence, namely the 5% significant test, planning had a positive and insignificant effect on team capability, planning had a positive and significant effect on sales support, team capability had a significant and positive effect on company performance, and sales support had a positive but not significant effect on company performance. Meanwhile, in the 10% significant test, it was found that changes in the planning relationship on team capabilities had a positive and significant effect on sales support.